COLDS IN CHILDREN. HOW TO TREAT A RUNNING NOSE? - E. P. Karpova; D. A. Tulupov; M. P. Vorobieva (Медицинский совет, 2016)
The acute respiratory viral infection (ARVI, in the English literature the term «common cold» is used) – is an acute, in most cases a self-limiting  infection of the  respiratory tract, manifested by catarrhal inflammation of the  upper respiratory tract and occurring with fever, running nose, sneezing, cough, sore throat, a disturbance of the general condition of varying severity [1]. The common cold is one of the most common diseases in the world [2]. Adults suffer 2 to 5 episodes of colds per year and children – up to 7–10 [3]. Children under 5 years of age suffer at the average 6–8  episodes  of ARVI  [4, 5]. In preschool institutions especially the incidence is high during the 1-2 years of visit, which is by 10–15% higher than that of non-organized children, but in school these children get sick more often [6].